Karakteristik Penderita Kanker Payudara dengan Metastasis Jauh Tunggal di Kota Padang Tahun 2014-2018 - Muhammad Reno Akhyar Marpaung; Daan Khambri; Asterina Asterina (Jurnal Ilmu Kesehatan Indonesia, 2021)
Introduction: Breast cancer is the most common malignancy in women. Distant metastases are the main cause of death in breast cancer. Objective : To determine the characteristics of breast cancer sufferers with distant metastases. Method: This study is descriptive study with cross-sectional design. The sample of this study were all breast cancer patients with single distant metastases in RSI Ibnu Sina and RSK Ropanasuri Surgery Padang in 2014-2018 with a minimum sample is 97. The research instruments used were medical records and breast cancer registration sheets. Results: The results of this study found 136 cases of breast cancer with the most distant metastases to the lungs 42%, bones 33%, liver 12%, brain 8%, and other organs 5%. The mean age of patients was 47.5 years, with the most histopathological type, namely IDC 63.2%. Mostly education level was high 41.9%. Most examination of body mass index was overweight / obese 64.7%. According to menarche history was normal 79.4%. Based on the examination, the most tumor size that was T4 52.9% and the most nodule size was N1 50.7% with the most molecular subtypes was Luminal A as much as 34.6%. Conclusion: Most breast cancer with distant metastasis goes to lungs.